Morbidity and functional ability in the elderly: a cross sectional study in a rural population of Manipur - Devi, Ningombam Joenna; Rajkumari, Bishwalata; Devi, Longjam Usharani (International Journal Of Community Medicine And Public Health, 2020)
Background: Elderly in India suffers from both communicable and non-communicable diseases, also functional independence reduces due to physiological changes. This study aims to determine the pattern of morbidity, functional ability in activities of daily living (ADL), instrumental activities of daily living (IADL) and to assess any factors associated with ADL. Methods: A cross-sectional study was conducted from May 2017 to April 2019 among 420 elderly aged 60 years and above residing in rural areas of Wangoi in Manipur. Probability proportional to size (PPS) sampling method was used to select 6 villages out of 28 villages. A pre-tested interview schedule was used as study tool. Data were analysed using SPSS IBM statistics version 21 using mean, SD, proportion, chi-squared (χ²) test, univariate and multivariate logistic regression analysis were performed taking p-value<0.05 as statistically significant. Results: Some form of morbidity was reported by 49.1% of the respondents. The prevalence of dependent according to ADL was 8.1%. According to IADL score, 97.6% female and 46% male have limitation. Elder age group, female gender, living without spouse, illiterate were significantly associated with dependency according to ADL. In adjusted analysis, every unit increased in age, risk of being dependent increases significantly by 10% [AOR=1.10 (1.04-1.16)]. Conclusions: Almost half of respondents had some form of morbidity. Only a few (4.5%) were dependent according to ADL. A more comprehensive study covering different communities using various laboratory investigations can be conducted in Manipur.